Understanding the Evolution of an Oceanic Intraplate Volcano From Seismic Reflection Data: A New Model for La Réunion, Indian Ocean. Issue 2 (20th February 2018) - Lebas, E.; Le Friant, A.; Deplus, C.; de Voogd, B.
Abstract: High‐resolution seismic reflection profiles gathered in 2006 on La Réunion submarine flanks and surrounding abyssal plain, enabled characterization of the seismostratigraphy architecture of the volcaniclastic apron. Four seismic units are defined beyond the edifice base: (1) a basal unit, interpreted as pelagic sediment predating La Réunion volcanism; (2) a second unit showing low‐ to medium‐amplitude reflections, related to La Réunion emergence including the submarine explosive phase; (3) a high‐amplitude seismic unit, associated with subaerial volcanic activity (i.e., mature island stage); and (4) an acoustically transparent unit, ascribed to erosion that currently affects the volcanic complex. Two prominent horizons delineate the base of the units II and III marking, respectively, the onset of La Réunion seamount explosive activity and the Piton des Neiges volcanic activity. Related isopach maps demonstrate: (1) the existence of a large proto‐Piton des Neiges volcano during the first building phase of the volcanic complex, and (2) the central role of the Piton des Neiges volcano during the second phase. Shield growth stage of the Piton de la Fournaise volcano is also captured in the upper part of the volcaniclastic apron, attesting to its recent contribution. Seismic facies identified in the apron highlight a prevalence of sedimentary and reworking processes since the onset of the volcanism compared to catastrophic flank collapses. We present here a new model of evolution for La Réunion volcanic complex since the onset of the volcanism and argue that a major proto Piton des Neiges‐Piton des Neiges volcanic complex controls La Réunion present‐day morphology. Key Points: Multichannel seismic imaging reveals the seismostratigraphy architecture of La Réunion volcaniclastic apron Prevalence of gradual degradation/dismantling processes on large flank collapse events Control of La Réunion present‐day morphology by a major proto Piton des Neiges‐Piton des Neiges volcanic complex